2002
DOI: 10.1093/jpepsy/27.7.593
|View full text |Cite
|
Sign up to set email alerts
|

Living With a Chronic Illness: A Measure of Social Functioning for Children and Adolescents

Abstract: These findings support the initial psychometric properties and clinical utility of the LCI scores. We discuss strengths and limitations of this study, as well as potential clinical applications for the LCI questionnaire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 17 publications
2
41
0
Order By: Relevance
“…Researchers have found higher rates of social problems in children with epilepsy (Hoare 1993, Mitchell et al 1994, Wilde and Haslam 1996, Brantley et al 2002 and in children with mental retardation (Guralnick 1997). Our findings are consistent with previous studies suggesting that low IQ is associated with more social problems (Espie et al 1989, Sabaz et al 2001, Adams et al 2002. Sabaz et al (2001) reported that children with epilepsy and an IQ score below 70 experience problems in the areas of social interactions and social activities.…”
Section: Cbclsupporting
confidence: 93%
“…Researchers have found higher rates of social problems in children with epilepsy (Hoare 1993, Mitchell et al 1994, Wilde and Haslam 1996, Brantley et al 2002 and in children with mental retardation (Guralnick 1997). Our findings are consistent with previous studies suggesting that low IQ is associated with more social problems (Espie et al 1989, Sabaz et al 2001, Adams et al 2002. Sabaz et al (2001) reported that children with epilepsy and an IQ score below 70 experience problems in the areas of social interactions and social activities.…”
Section: Cbclsupporting
confidence: 93%
“…Inclusion criteria for participation in the present study were as follows: the child (1) had a diagnosis of a JRD, (2) was between the ages of 9 and 17 years, and (3) the duration of the child's disease symptoms had been at least 6 months. Exclusion criteria for participants were as follows: the child had (1) comorbid cognitive deficits (e.g., mental retardation) that precluded him/her from understanding the protocol tasks and (2) a comorbid chronic illness.…”
Section: Participantsmentioning
confidence: 99%
“…The chronic episodic nature of these illnesses creates particular challenges for children to engage in pleasurable and valued activities as well as ordinary daily self-care and presents potential social challenges similar to those experienced by children with other chronic illnesses (e.g., Ref. [2]). Efforts to carry out normal and desired activities are also impacted by the high degree of functional disability often experienced throughout the disease course.…”
Section: Introductionmentioning
confidence: 99%
“…There are many different and complex psychosocial factors affecting all individuals with HIV infection [26]. Selected key points are highlighted, namelya) Paediatric patients experience stages and stresses similar to other paediatric chronic conditions b) Stigma affects all aspects of caring for these children and adolescents and especially during the disclosure and acceptance period c) Death and bereavement must be openly discussed for the children and the families d) Orphans, vulnerable groups and young girls are at an increased risk of contracting sexually transmitted infections and may receive less support and education than their peers e) And adolescents remain a unique population who can be described as having a pivotal role in the future of the HIV pandemic in developed and developing countries.…”
Section: Psychosocial Issues and Practical Points Of Carementioning
confidence: 99%